2022
DOI: 10.3389/fmicb.2022.910277
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Threshold Values of Multi-Locus Sequence Analysis, Average Nucleotide Identity and Digital DNA–DNA Hybridization in Delineating Streptomyces Species

Abstract: Multi-locus sequence analysis (MLSA) has been proved to be a useful method for Streptomyces identification and MLSA distance of 0.007 is considered as the boundary value. However, we found that MLSA distance of 0.007 might be insufficient to act as a threshold according to the correlations among average nucleotide identity based on MuMmer ultra-rapid aligning tool (ANIm), digital DNA–DNA hybridization (dDDH) and MLSA from the 80 pairs of Streptomyces species; in addition, a 70% dDDH value did not correspond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The comparative analysis based on 16S rRNA gene sequence similarity of strain T5 T showed highest sequence similarity (99.0 % pairwise similarity) to Streptomyces lichenis LCR6-01 T (LC360144). The MLSA distance between strain T5 T and S. lichenis LCR6-01 T was 0.036 which was above the recommended threshold (≥0.014) for species delineation [25]. Similarly, the strain T5 T and S. lichenis LCR6-01 T gene sequences of gyrB, recA, rpoB and trpB used in MLSA also showed pairwise sequence similarities of 96.6, 95.0, 98.2 and 96.1 %, respectively, which were lower than the recommended threshold for species delineation (gyrB, <99.0 %; recA, <99.5 %; rpoB, <99.6 % trpB, <97.9 %) [26].…”
Section: Molecular Characterisationmentioning
confidence: 75%
See 1 more Smart Citation
“…The comparative analysis based on 16S rRNA gene sequence similarity of strain T5 T showed highest sequence similarity (99.0 % pairwise similarity) to Streptomyces lichenis LCR6-01 T (LC360144). The MLSA distance between strain T5 T and S. lichenis LCR6-01 T was 0.036 which was above the recommended threshold (≥0.014) for species delineation [25]. Similarly, the strain T5 T and S. lichenis LCR6-01 T gene sequences of gyrB, recA, rpoB and trpB used in MLSA also showed pairwise sequence similarities of 96.6, 95.0, 98.2 and 96.1 %, respectively, which were lower than the recommended threshold for species delineation (gyrB, <99.0 %; recA, <99.5 %; rpoB, <99.6 % trpB, <97.9 %) [26].…”
Section: Molecular Characterisationmentioning
confidence: 75%
“…The MLSA distance between strain T5 T and S. lichenis LCR6-01 T was 0.036 which was above the recommended threshold (≥0.014) for species delineation [25]. Similarly, the strain T5 T and S.…”
Section: Molecular Characterisationmentioning
confidence: 97%
“…2B ). In a recent study, a 70% dDDH corresponded to approximately 96.7% and not the 95 to 96% cutoff point in delineating Streptomyces species ( 27 ). These findings suggested that S. tubbatahanensis DSD3025 T is a novel species based on the MLSA, dDDH, and orthoANI values between S. tubbatahanensis DSD3025 T and its closest match, S. diacarni LHW51701 T .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the ANI and dDDH values between the whole-genome sequences of strain BH-MK-02 T and S. aureus CGMCC 4.1833 T were 78.1 and 23.2 %, respectively, below the 96.7 and 70 % cut-off points recommended for delineating Streptomyces species [44, 45], suggesting that BH-MK-02 T represents a novel species of the genus Streptomyces . This result was further confirmed by phenotypic differences between strain BH-MK-02 T and S.…”
Section: Resultsmentioning
confidence: 99%